Growth and Production of Anogeissus Pendula (Edgw.)-based Silvopastoral System under Different Pruning Managements - Rai, P; Rao, G R; Yadav, R S; Handa, A K; Charuvedi, O P (Annals of Arid Zone, 2016)
.Â